Phacomatosis pigmentokeratotica: two cases series of a neurocutaneous rarity from Indonesia - Retno Danarti; Nafiah Chusniyati; Yuli Sulistiyowati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Phacomatosis pigmentokeratotica (PPK) is a distinct epidermal naevus syndrome. The syndrome is characterized by the coexistence of an organoid naevus with sebaceous differentiation arranged along Blaschko's lines, a papular naevus spilus arranged in a checkerboard pattern, in association with other extracutaneous anomalies. We report on two cases of PPK. The first case was an 11-year-old girl with sebaceous naevus on the right side of the body following the lines of Blaschko present since birth, whereas a papular naevus spilus involving the dorsal area of the neck was noted at 8 years of age. The second case was a 15-year old girl presented with sebaceous naevus on her face and neck and papular naevus spilus involving left side of her chest. Electroencephalography (EEG) of both cases revealed abnormal irritative epileptiform waves, and brain mapping showed symmetrical structures and no focus. The diagnoses of our two cases were based on clinical pictures of the coexistence of sebaceous naevus arranged along Blaschko's lines, a papular naevus spilus arranged in a checkerboard pattern, and EEG anomalies. To our knowledge, these cases were first reported in Indonesia. The association with various extracutaneous manifestation is often, as well as the possibility of malignant transformation.Hence a close follow-up of PPK patients is important, which may help in early recognition of the development of extracutaneous anomalies and the possibility of malignant transformation.